Neurofilament light chain as a biological marker for amyotrophic lateral sclerosis: a meta-analysis study. Issue 5 (3rd July 2022) - Sferruzza, Giacomo; Bosco, Luca; Falzone, Yuri Matteo; Russo, Tommaso; Domi, Teuta; Quattrini, Angelo; Filippi, Massimo; Riva, Nilo
Abstract: Aim: The aim of the present metanalysis is to evaluate blood and CSF Neurofilament light chain (NfL) concentrations in ALS patients, compared to healthy controls, ALS mimic disorders (ALSmd) and other neurological diseases (OND), and to evaluate their diagnostic yield against ALSmd. Methods : Search engines were systematically investigated for relevant studies. A random effect model was applied to estimate the pooled standard mean difference in NfL levels between ALS and controls and a bivariate mixed-effects model was applied to estimate their diagnostic accuracy on blood and CSF. Results and conclusions : NfL CSF levels were higher in ALS compared with all other control groups. On blood, NfL levels were significantly higher in ALS patients compared with healthy controls and ALSmd. In a subgroup analysis, the use of SIMOA yielded to a better differentiation between ALS and controls on blood, compared with ELISA. Studies performed on CSF (AUC = 0.90) yielded to better diagnostic performances compared with those conducted on blood (AUC = 0.78). Further prospective investigations are needed to determine a diagnostic cutoff, exploitable in clinical practice.